(untitled) (Journal of Asian Development Studies, 2015)
Contemporarily in Andhra Pradesh due to climate change, monocropping and intensification of resources, there is a shift in cropping pattern from low value crops to high value crops. Further there is also reduction in productivity of food crops over the years, but the magnitude and direction of change is unknown. To understand the situation the growth rates of major crops of Andhra Pradesh were studied using the time series data from 1980-81 to 2009-2010. The growth pattern was examined by fitting on exponential function (Y=ABt). Growth rates showed a significant positive growth in area under pulses, oilseeds, commercial crops, fruits and vegetables while cereals showed significant negative growth. The area under rice, jowar, bajra, and ragi are experiencing a substantial annual declining trend. The growth in area under total oilseeds and commercial crops except tobacco has recorded a mild annual increment. Similarly the production of High yielding varieties of cereals, pulses, oilseeds, commercial crops, vegetables and fruits showed a significant positive growth. The productivity of different crops recorded significant growth in the case of cereals, pulses and commercial crops. Productivity of oilseeds and fruits recorded moderately positive growth. The productivity of vegetables registered was highly significant and positive growth. It is concluded that the crops viz., maize, pulses, oilseeds, cotton, fruits and vegetables showed better performance during the entire period of the study. This indicates transformation in cropping pattern from redundant low valued crops to high valued commercial crops.